Family Satisfaction of Covid-19 Patients with the Information Delivery Process and Hospital Services - Heru Noor Ramadhan; Angilian Budi Ardhianto; Elly Yuliastuti; Tujo Tujo; Amin Husni; Retnaningsih Retnaningsih (Universitas Muhammadiyah Semarang, 2021)
Patients /Family patients satisfaction is an indicator to assess the quality of a hospital. During the Covid-19 pandemic, several problems emerged related to the quality of information provision and services provided. The purpose of this study was to describe the family satisfaction of Covid-19 patients with the provision of information and services provided. This research is a quantitative observational descriptive study with a variable of family satisfaction of covid-19 patients with the information and services provided. The population in this study is the families (husband / wife) of patients who recovered and were treated in the Covid-19 Isolation Ward RSUP dr. Kariadi Semarang with totaling 40 people. Sampling was done by using purposive sampling technique and the resulting sample was 30 respondents. Measurement of variables using a questionnaire providing information and service delivery. The results showed that the average patient's family expressed satisfaction with the provision of information (> 30) and services provided (>42). Innovation is needed to further improve service quality so that service quality will be even better.